Instructional technologies of education in East African countries: An overview - Faustino, Anagrolia; Kaur, Guneet; Bussey, Marcus (Journal of Interdisciplinary Studies in Education, 2024)
This paper investigates the use of commonly employed technologies in education across East African countries, specifically focusing on Tanzania, Kenya, Uganda, Rwanda, and Sudan. It draws on Google Scholar to identify key technologies used in teaching and learning, emphasizing their benefits, such as increased student engagement, commitment, interaction, and improved performance. However, several challenges hinder the effective use of these technologies, including unfamiliarity, time constraints, negative attitudes, lack of human resources, insufficient government support, and infrastructure limitations. To overcome these obstacles, the paper recommends providing teachers with better training and workshops on accessing and utilizing appropriate technological tools. Furthermore, it calls for enhanced government involvement to ensure modern technologies are effectively integrated, thereby improving the overall quality of education in the region.